A method for preparing a carbon-based hierarchical mesoporous electrode material of a biomass-resin composite

CN120664684BActive Publication Date: 2026-10-16HARBIN INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510811092.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-17
Publication Date
2026-10-16
Estimated Expiration
2045-06-17

AI Technical Summary

Technical Problem

[0007]本发明针对微生物电化学系统中电极-生物膜界面电子转移效率及化学能-电能转化效率低等问题,开发了生物质-树脂复合材料的碳基分级次多孔生物电极材料的制备方法及其应用,本发明利用可再生的生物质资源,实现高性能、低成本、分级次多孔碳基电极材料的灵活可控制备,并通过与工业树脂材料复合,强化碳基电极的机械性能和改性效果

Benefits of technology

(1)本发明制备的新型生物质-树脂碳基分级次多孔生物电极材料,使用废弃生物质和低成本的工业化树脂,原料来源广制备步骤简单,大大削减了构建成本,更适用于生物电化学系统规模化应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120664684B_ABST
    Figure CN120664684B_ABST
Patent Text Reader

Abstract

The application relates to a preparation method of a carbon-based hierarchical sub-porous bioelectrode material of a biomass-resin composite, and belongs to the technical field of microbial electrochemistry, and particularly relates to a preparation method of a porous bioelectrode material.The application is aimed at the problems of low electron transfer efficiency at the electrode-biofilm interface and low chemical energy-electric energy conversion efficiency in a microbial electrochemical system, utilizes renewable biomass resources, realizes flexible and controllable preparation of a high-performance, low-cost, hierarchical sub-porous carbon-based electrode material, and strengthens the mechanical performance and modification effect of the carbon-based electrode by being combined with industrial resin materials. Industrial resin matrices are introduced as structural supports and conductive media, the combination of resin polymers can effectively improve mechanical defects and enhance durability, the resin materials can act as structural supports, conductive media, and can realize target element doping and chemical modification by flexibly changing synthetic monomers or adding other components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of microbial electrochemistry technology, specifically relating to a method for preparing a carbon-based hierarchical subporous bioelectrode material based on biomass-resin composite materials. Background Technology

[0002] Currently, most wastewater treatment processes focus on pollutant removal while neglecting the resource utilization of wastewater. The high material consumption, high energy consumption, and high carbon emissions of traditional wastewater treatment have become a bottleneck for the low-carbon development of my country's water treatment industry. Energy consumption accounts for 25% to 40% of the operating costs of traditional wastewater treatment plants, with electricity consumption accounting for 3% of global electricity consumption. The aeration stage, the most energy-intensive stage, consumes 50% to 60% of the total electricity. Furthermore, the greenhouse gas emissions generated during traditional wastewater treatment and the indirect greenhouse gas emissions from wastewater energy consumption are enormous. The chemical energy contained in the organic matter in wastewater is a potential energy source; theoretically, 1L of chemical oxygen demand (COD) is 500 mg / L. -1 Complete oxidation of domestic sewage can produce 1.93 kWh. -3 Electrical energy.

[0003] Bioelectrochemical technology offers a promising solution to meet my country's low-carbon strategy in wastewater treatment. Electroactive microorganisms are those capable of bidirectional electron and energy exchange with the external environment via extracellular electron transfer, including electrogenic microorganisms that release electrons to the environment and electrophilic microorganisms that receive electrons from the environment. Microbial electrochemical systems (MES) share the common characteristic of utilizing electron and energy exchange between electroactive microorganisms and the external environment. The anode is the primary site for efficient pollutant removal; electrogenic microorganisms oxidize organic pollutants, releasing electrons to the anode, achieving efficient pollutant degradation while serving as a continuous electron source. The cathode is a crucial unit for expanding the functions of the MES; electrophilic microorganisms utilize electrons from the anode to bind with different acceptors, enabling multiple functions such as wastewater energy recovery, denitrification, and CO2 catalytic synthesis. Related wastewater energy resource recovery technologies derived from bioelectrochemical technology are expected to play a significant role in "pollution reduction and carbon reduction" in water treatment processes.

[0004] The core bottleneck limiting the performance of bioelectrochemical systems is the low electron transfer efficiency between the electrode and microorganisms. The core process of microelectrochemical excision scalars (MES) is the exchange of electrons and energy between electroactive bacteria and electrodes. Improving the electron transfer rate at the electrode material-microorganism interface directly promotes functional indicators in MES, such as the decomposition efficiency of organic pollutants, the extraction rate of energy-generating gases, and the rates of CO2 fixation and chemical synthesis. This is a necessary requirement for achieving techno-economic viability in MES. Electrodes serve as the habitat and site for electron and energy exchange for electroactive microorganisms. Revealing the electrode-microorganism interaction processes at multiple scales, overcoming key material and mechanistic bottlenecks, and constructing an efficient electrode-microorganism electron transfer system are of great significance for the application and large-scale expansion of bioelectrochemical technology.

[0005] Carbon-based electrode materials are widely used in microbial electrochemical systems due to their excellent conductivity and stable physicochemical properties. Among them, commercially available two-dimensional materials such as carbon cloth and carbon paper were the earliest and most widely used, but they are expensive and have relatively limited usable surface area. To further reduce material preparation costs, increase specific surface area, and improve electrode performance, three-dimensional carbon-based materials with abundant pore structures and more bioaccessible surface area have become a research hotspot. Key characteristics of efficient three-dimensional MES electrode materials include low cost, high conductivity, large specific surface area, excellent mechanical properties, and biocompatibility. Among them, carbon brushes (CB) are considered to be one of the best-performing commercial carbon-based materials, but their columnar structure leads to large electrode spacing, which is not conducive to space saving and dense stacking engineering applications of modular MES, and their cost is too high and modification is difficult. In contrast, planar carbon cloth (CC), carbon felt (CF), and carbon paper (CP) materials are widely used in MES, but these materials are limited by relatively low specific surface area, poor conductivity, and lack of capacitive buffering capacity. Capacitive anodes are crucial in MES (Mechanical Engineering System) because they can rapidly store and release electrons, improving electron transfer efficiency in electrochemical reactions, while also buffering electrode potential fluctuations to ensure stable system operation. To improve capacitive performance, materials such as activated carbon, carbon nanotubes, and graphene are often introduced into carbon-based matrices. While these additives can increase specific surface area and optimize pore structure, they still cannot simultaneously provide the high bioavailable surface area required for external bacterial colonization.

[0006] Widely available and inexpensive biomass-derived materials offer another option. First, biomass is a renewable energy source, consisting of carbon dioxide fixed by sunlight. Second, biomass is composed of cellular structures and can be converted into porous carbon materials through pyrolysis and activation. Third, biomass contains various elements, and certain biomass with specific enrichment properties can be used as precursors to introduce heteroatoms at low cost during carbonization, providing more active sites for carbon-structured electrodes without incurring additional costs. Currently, natural biomass-derived carbon, such as silkworm cocoons, corn cobs, and coffee grounds, has been explored as electrode materials for MES (Mechanical Engineering). Some studies have also focused on nitrogen (N) and oxygen (O) doping in biomass, but research on other potentially important elements such as iron (Fe) and manganese (Mn) from the perspective of biomass precursors is limited, and related research and applications urgently need to be promoted. At the same time, simple biomass carbonization has inherent defects, including insufficient mechanical strength, uncontrollable carbon structure and composition, limited long-term operational stability, and significant performance fluctuations due to differences in raw material sources, which seriously hinder its large-scale application. Summary of the Invention

[0007] This invention addresses the low electron transfer efficiency and chemical-to-electrical energy conversion efficiency at the electrode-biofilm interface in microbial electrochemical systems. It develops a method for preparing carbon-based hierarchical subporous bioelectrode materials using biomass-resin composites and their applications. This invention utilizes renewable biomass resources to achieve flexible and controllable preparation of high-performance, low-cost, hierarchical subporous carbon-based electrode materials. Furthermore, by combining these materials with industrial resins, the mechanical properties and modification effects of the carbon-based electrode are enhanced. The high-performance carbon electrode of this invention can enhance electron transfer at the biofilm-electrode interface, bioelectron storage, and the enrichment of electrogenic microorganisms, while simultaneously removing contaminants and strengthening the electricity generation of the microbial electrochemical system. This invention introduces an industrial-grade resin matrix as a structural support and conductive medium. The composite of the resin polymer effectively improves mechanical defects and enhances durability. The industrial-grade resin material is low-cost, with a carbon residue of up to 60% after high-temperature pyrolysis, offering advantages in electrode material preparation such as design flexibility and stable performance. The resin material can serve as a structural support and conductive medium, and by flexibly changing the synthetic monomers or adding other components, it can achieve target element doping, chemical modification, and specific electrochemical functions.

[0008] The preparation method of the carbon-based hierarchical subporous bioelectrode material of the biomass-resin composite material of the present invention is carried out according to the following steps: I. Preparation of Resin Precursors: ① Phenolic resin is synthesized using formaldehyde and phenol, and melamine is added to the phenolic resin for formaldehyde substitution modification to obtain melamine-modified phenolic resin. The alkaline catalyst is a 20% NaOH solution; the alkaline catalyst is 5% to 15% of the mass of phenol, and the melamine is 5% to 30% of the mass of phenol; a large amount of melamine will affect the polymerization reaction. If the unreacted melamine forms a white precipitate, the reaction time should be extended.

[0009] ② Preparation of iron-nitrogen co-doped resin: Cool the melamine-modified phenolic resin from step ① to 25~50℃, add the pre-dissolved iron source solution, and react for 10~60 minutes to obtain iron-nitrogen co-doped resin. The mass of the iron source in the iron source solution is 1% to 12% of the mass of phenol; too much iron source will affect the polymerization reaction of the resin and the mechanical properties of the target material; too little iron source will affect the modification effect.

[0010] II. Biomass Precursor Preparation After washing and drying, the biomass is pulverized to obtain biomass powder with a mesh size of 60-100. III. Activation of Biomass Precursors The biomass powder obtained in step two is co-dispersed with the activator in deionized water to obtain a mixture. The mixture is stirred at 30-60°C for 8-12 hours and then freeze-dried to obtain the activated biomass precursor. The mass ratio of the biomass powder to the activator is 1:0.5~4; IV. Biomass precursor precarbonization The activated biomass precursor obtained in step three is pre-carbonized to obtain a pre-carbonized biomass precursor. The pre-carbonization process is as follows: in an inert gas atmosphere, at 1~5℃ min... -1 Heating to 300-400℃ at a rate of [missing information] and maintaining for 30-60 minutes; the inert gas is N2, and the inert gas flow rate is 80-120 mL / min. -1 ; V. Preparation of Composite Carbonization Precursors The iron-nitrogen co-doped resin obtained in step one, the pre-carbonized biomass precursor obtained in step four, and the plastic microparticle sacrificial template are mixed evenly, and the mixture is cured at 90~140°C for 6~14 hours to obtain the composite carbonized precursor. The sacrificial template for the plastic microparticles is 1-10% of the mass of the iron-nitrogen co-doped resin; The pre-carbonized biomass precursor is 30-70% of the iron-nitrogen co-doped resin. If there is too much pre-carbonized biomass precursor, it will reduce the viscosity of the composite slurry and the mechanical properties of the target material; if there is too little pre-carbonized biomass precursor, it will reduce the electrochemical properties and other attributes of the target material. The plastic microparticle sacrificial template is a plastic microparticle made of polyethylene (PE), polylactic acid (PLA), polyamide (PA), polystyrene (PS), polyoxymethylene (POM), or polymethyl methacrylate (PMMA). VI. Carrier Gas Protected Carbonization High-Temperature Pyrolysis Under an inert gas atmosphere, the composite carbonization precursor obtained in step five is heated at 1~8℃ for min. -1 The heating rate is increased to 700~1000℃, and high-temperature pyrolysis is carried out for 1~3 hours to obtain high-temperature pyrolysis material; if the heating / cooling rate is too fast, it will affect the structure of the target material during the calcination process; if the heating / cooling rate is too slow, it will reduce the preparation efficiency. VII. Desalting and Impurity Removal of Carbonized Electrode The high-temperature pyrolysis material obtained in step six was desalted and impurities removed using deionized water to obtain a carbon-based hierarchical subporous bioelectrode material.

[0011] This invention develops a method for constructing a capacitive carbon electrode material based on biomass-modified resin. The multi-level subporous structure of the electrode material is established using an activator and a sacrificial template, while the heteroatom structure is formed using biomass and modified resin. These elements synergistically achieve high capacitance and a low energy barrier interface. When applied to microbial electrochemical systems, this electrode material can withstand high current surges and promote interfacial electron transport through an electron storage tank and electron transfer pathway, achieving breakthrough current and power densities while simultaneously enhancing pollutant removal.

[0012] Compared with the prior art, the beneficial effects of the present invention are: (1) The novel biomass-resin carbon-based hierarchical subporous bioelectrode material prepared by the present invention uses waste biomass and low-cost industrial resin. The raw materials are widely available and the preparation steps are simple, which greatly reduces the construction cost and makes it more suitable for large-scale application in bioelectrochemical systems.

[0013] (2) The novel biomass-resin carbon-based hierarchical subporous bioelectrode material prepared by this invention has high mechanical properties, hierarchical subporous structure, high capacitance and low resistance, and good biocompatibility, which can significantly promote the attachment of electroactive bacteria and the storage of biocharge. Compared with traditional carbon electrodes, it has a shorter start-up time, faster biofilm acclimation speed, and more stable operation.

[0014] (3) The porous carbon electrode material prepared by the present invention has a fast degradation rate of organic wastewater, high chemical energy to electrical energy conversion efficiency, and higher coulombic efficiency than the same type of electrode; the maximum power density is more than 3 times that of the traditional carbon electrode, and the maximum current density is more than 4 times that of the traditional carbon electrode.

[0015] (4) The porous carbon electrode material prepared by the present invention can efficiently and selectively enrich electrogenic bacteria and effectively promote the formation of electroactive biofilms. Based on the iron, nitrogen, oxygen and other elements introduced by biomass doping, interfacial active sites are formed, which promote the copy abundance of genes related to direct extracellular electron transfer and have a promoting effect on electron transfer at the bio-electrode interface.

[0016] (5) The porous carbon electrode material prepared by this invention can be prepared by molding and is easy to shape. The shape change during the carbonization process is small, and it is easy to prepare porous carbon electrodes of various sizes and with neat shapes to meet the needs of bioelectrochemical systems of different scales.

[0017] (6) The porous carbon electrode material prepared by this invention has multiple pore sources, including pores from the resin carbonization process, pores from biomass porous structures, pores from sacrificial pore-forming templates, and carbonized pores at the interface between biomass particles and resin precursors. The above-mentioned pores form multi-level pores ranging from nanometers to hundreds of micrometers. These porous structures can provide conditions for material transport in bioelectrochemical systems (hundreds of micrometers to millimeters of macroscopic pores), attachment of electroactive microorganisms (1 to 100 micrometers), and catalytic conversion of "chemical energy to electrical energy" (nanometers to 1 micrometer). Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the microbial electrochemical system (MES) in the embodiment; Figure 2 Scanning electron microscope image of the carbon-based hierarchical subporous bioelectrode material prepared for control group 2; Figure 3 A scanning electron microscope image of the carbon-based hierarchical subporous bioelectrode material prepared in Example 1; Figure 4 This is a scanning electron microscope image of the carbon-based hierarchical subporous bioelectrode material prepared in Example 2; Figure 5 This is a scanning electron microscope image of the carbon-based hierarchical subporous bioelectrode material prepared in Example 3; Figure 6 The cyclic voltammetry curves of the carbon-based hierarchical subporous bioelectrode material prepared in the examples are shown below. Figure 7 The diagram shows the cumulative charge and coulombic efficiency of the microbial electrochemical system during a single cycle in the examples. Figure 8 The power density curve of the biofilm formed on the carbon-based hierarchical subporous bioelectrode material in the embodiment is shown. Figure 9 The diagram shows the capacitance charge on the carbon-based hierarchical subporous bioelectrode material in the embodiment. Figure 10This is a diagram of biomass on the carbon-based hierarchical subporous bioelectrode material in the embodiment; Figure 11 The diagram shows the community composition and abundance on the carbon-based hierarchical subporous bioelectrode material in the examples. Detailed Implementation

[0019] The technical solution of the present invention is not limited to the specific embodiments listed below, but also includes any reasonable combination of the specific embodiments.

[0020] Specific Implementation Method 1: The preparation method of the carbon-based hierarchical subporous bioelectrode material of biomass-resin composite material in this implementation method is carried out according to the following steps: I. Preparation of Resin Precursors: ① Phenolic resin is synthesized using formaldehyde and phenol, and melamine is added to the phenolic resin for formaldehyde substitution modification to obtain melamine-modified phenolic resin. The alkaline catalyst is a 20% (w / w) NaOH solution; the alkaline catalyst is 5% to 15% (w / w) of phenol, and the melamine is 5% to 30% (w / w) of phenol. ② Preparation of iron-nitrogen co-doped resin: Cool the melamine-modified phenolic resin from step ① to 25~50℃, add the pre-dissolved iron source solution, and react for 10~60 minutes to obtain iron-nitrogen co-doped resin. The mass of the iron source in the iron source solution is 1% to 12% of the mass of phenol; II. Biomass Precursor Preparation After washing and drying, the biomass is pulverized to obtain biomass powder with a mesh size of 60-100. III. Activation of Biomass Precursors The biomass powder obtained in step two is co-dispersed with the activator in deionized water to obtain a mixture. The mixture is stirred at 30-60°C for 8-12 hours and then freeze-dried to obtain the activated biomass precursor. The mass ratio of the biomass powder to the activator is 1:0.5~4; IV. Biomass precursor precarbonization The activated biomass precursor obtained in step three is pre-carbonized to obtain a pre-carbonized biomass precursor. The pre-carbonization process is as follows: in an inert gas atmosphere, at 1~5℃ for min... -1 Heating to 300-400℃ at a rate of [missing information] and maintaining for 30-60 minutes; the inert gas is N2, and the inert gas flow rate is 80-120 mL / min. -1 ; V. Preparation of Composite Carbonization Precursors The iron-nitrogen co-doped resin obtained in step one, the pre-carbonized biomass precursor obtained in step four, and the plastic microparticle sacrificial template are mixed evenly, and the mixture is cured at 90~140°C for 6~14 hours to obtain the composite carbonized precursor. The sacrificial template for the plastic microparticles is 1-10% of the mass of the iron-nitrogen co-doped resin; The pre-carbonized biomass precursor comprises 30-70% of the iron-nitrogen co-doped resin by mass. The plastic microparticle sacrificial template is a plastic microparticle made of polyethylene, polylactic acid, polyamide, polystyrene, polyoxymethylene or polymethyl methacrylate. VI. Carrier Gas Protected Carbonization High-Temperature Pyrolysis Under an inert gas atmosphere, the composite carbonization precursor obtained in step five is heated at 1~8℃ for min. -1 The temperature is increased to 700~1000℃ at a heating rate, and then pyrolyzed at high temperature for 1~3 hours to obtain high-temperature pyrolysis material; VII. Desalting and Impurity Removal of Carbonized Electrode The high-temperature pyrolysis material obtained in step six was desalted and impurities removed using deionized water to obtain a carbon-based hierarchical subporous bioelectrode material.

[0021] (1) The novel biomass-resin carbon-based hierarchical subporous bioelectrode material prepared in this embodiment uses waste biomass and low-cost industrial resin. The raw materials are widely available and the preparation steps are simple, which greatly reduces the construction cost and makes it more suitable for large-scale application in bioelectrochemical systems.

[0022] (2) The novel biomass-resin carbon-based hierarchical subporous bioelectrode material prepared in this embodiment has high mechanical properties, hierarchical subporous structure, high capacitance and low resistance, and good biocompatibility, which can significantly promote the attachment of electroactive bacteria and the storage of biocharge. Compared with traditional carbon electrodes, it has a shorter start-up time, faster biofilm acclimation speed, and more stable operation.

[0023] (3) The porous carbon electrode material prepared in this embodiment has a fast degradation rate of organic wastewater, high chemical energy to electrical energy conversion efficiency, and higher coulombic efficiency than the same type of electrode; the maximum power density is more than 3 times that of the traditional carbon electrode, and the maximum current density is more than 4 times that of the traditional carbon electrode.

[0024] (4) The porous carbon electrode material prepared in this embodiment can efficiently and selectively enrich electrogenic bacteria and effectively promote the formation of electroactive biofilms. Based on the iron, nitrogen, oxygen and other elements introduced by biomass doping, interfacial active sites are formed, which promotes the copy abundance of genes related to direct extracellular electron transfer and has a promoting effect on electron transfer at the bio-electrode interface.

[0025] (5) The porous carbon electrode material prepared in this embodiment can be molded and is easy to shape. The shape change during the carbonization process is small, and it is easy to prepare porous carbon electrodes of various sizes and with neat shapes to meet the needs of bioelectrochemical systems of different scales.

[0026] (6) The porous carbon electrode material prepared in this embodiment has multiple pore sources, including pores from the resin carbonization process, pores from the porous structure of biomass, pores from the sacrificial pore-forming template, and carbonized pores at the interface between biomass particles and resin precursors. The above-mentioned pores form multi-level pores ranging from nanometers to hundreds of micrometers. These porous structures can provide conditions for material transport in bioelectrochemical systems (macroscopic pores ranging from hundreds of micrometers to millimeters), attachment of electroactive microorganisms (1 to 100 micrometers), and catalytic conversion of "chemical energy to electrical energy" (nanometers to 1 micrometer).

[0027] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that: Step One ① The process for synthesizing phenolic resin is as follows: formaldehyde and phenol are placed in a three-necked flask, an alkaline catalyst is added, and the mixture is refluxed under a water bath heating condition of 75~85℃ for 0.5~1 hours; the molar ratio of formaldehyde to phenol is 1.3~1.8:1.

[0028] Specific Implementation Method 3: This implementation method differs from Specific Implementation Method 1 or 2 in that: the process of formaldehyde substitution modification in step 1① is as follows: melamine is added to the phenolic resin, and the mixture is refluxed under a water bath heating condition of 75~85℃ for 1.5~2 hours.

[0029] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that the iron source in the iron source solution described in step one ② is FeCl3, FeCl2, Fe(NO3), Fe(OAc)2, ferric acetylacetone, or ferric phthalate.

[0030] Specific Implementation Method 5: This implementation method differs from one of the specific implementation methods 1 to 4 in that the solvent in the iron source solution in step 1 ② is deionized water, N,N-dimethylformamide, or dimethyl sulfoxide.

[0031] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that the biomass mentioned in step two is spinach, wood ear fungus, shiitake mushroom, laver, seaweed, sea lettuce, or pumpkin seeds; and is a plant or algae with high iron content.

[0032] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One to Six in that the drying in step two is freeze drying at -20 to -80°C for 24 to 48 hours; or drying at 40 to 60°C for 24 to 48 hours.

[0033] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Methods One to Seven in that the freeze-drying temperature in step three is -20 to -80°C, and the drying time is 24 to 48 hours.

[0034] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that the activator mentioned in step three is ZnCl, KOH, KHCO3, K2FeO4, or NaOH.

[0035] Specific Implementation Method 10: This implementation method differs from Specific Implementation Methods 1 to 9 in that the desalting and impurity removal process described in step 7 is as follows: First, the electrode material is cleaned in deionized water until neutral, and then dried to complete the desalting; the desalted electrode material is soaked in an organic solvent for 1 to 6 hours to complete the impurity removal, and finally ultrasonically cleaned in deionized water for 20 to 60 minutes and dried; the organic solvent is anhydrous ethanol or acetone.

[0036] Example 1: The preparation method of the carbon-based hierarchical subporous bioelectrode material of biomass-resin composite material in this embodiment is carried out according to the following steps: I. Preparation of Resin Precursors: ① Phenolic resin is synthesized using formaldehyde and phenol, and melamine is added to the phenolic resin for formaldehyde substitution modification to obtain melamine-modified phenolic resin. The process for synthesizing phenolic resin is as follows: formaldehyde and phenol are placed in a three-necked flask, an alkaline catalyst is added, and the mixture is refluxed under a water bath heating condition at 80°C for 0.5 hours; the molar ratio of formaldehyde to phenol is 1.5:1. The process for formaldehyde substitution modification is as follows: melamine is added to the phenolic resin, and the mixture is refluxed under a water bath heating condition at 80°C for 2 hours. The alkaline catalyst is a 20% NaOH solution; the alkaline catalyst is 15% of the mass of phenol, and the melamine is 25% of the mass of phenol. ② Preparation of iron-nitrogen co-doped resin: The melamine-modified phenolic resin from step ① was cooled to 50°C, and a pre-dissolved iron source solution was added. The reaction was carried out for 30 minutes to obtain the iron-nitrogen co-doped resin. The iron source in the iron source solution is acetylacetone iron; The solvent in the iron source solution is N,N-dimethylformamide; The mass of the iron source in the iron source solution is 3% of the mass of phenol; II. Biomass Precursor Preparation After washing and drying, the biomass is pulverized to obtain 150μm biomass powder; The biomass is wood ear fungus: The drying process is freeze-drying at -50°C for 24 hours. III. Activation of Biomass Precursors The biomass powder obtained in step two was co-dispersed with the activator in deionized water to obtain a mixture. The mixture was stirred at 60°C for 10 hours and then freeze-dried to obtain the activated biomass precursor. The freeze-drying temperature is -50°C and the drying time is 48 hours.

[0037] The activator is KOH; The mass ratio of the biomass powder to the activator is 1:3; IV. Biomass precursor precarbonization The activated biomass precursor obtained in step three is pre-carbonized to obtain a pre-carbonized biomass precursor. The pre-carbonization process is as follows: in an inert gas atmosphere, at 5°C for 5 minutes... -1 The temperature was heated to 400°C and maintained for 60 minutes at a rate of [missing information]; the inert gas was N2, and the inert gas flow rate was 100 mL / min. -1 ; V. Preparation of Composite Carbonization Precursors 12g of the iron-nitrogen co-doped resin obtained in step one, 6g of the pre-carbonized biomass precursor obtained in step four, and 1.2g of plastic microparticle sacrificial template were mixed evenly, and the mixture was cured at 140°C for 6 hours to obtain the composite carbonized precursor. The sacrificial template for the plastic microparticles is made of plastic microparticles, specifically polyamide 6. VI. Carrier Gas Protected Carbonization High-Temperature Pyrolysis Under an inert gas atmosphere, the composite carbonization precursor obtained in step five was heated at 5°C for 1 minute. -1 The temperature was increased to 900℃ at a heating rate, and the material was pyrolyzed at high temperature for 2 hours to obtain the high-temperature pyrolysis material. VII. Desalting and Impurity Removal of Carbonized Electrode Desalting and impurity removal were performed on the high-temperature pyrolysis material obtained in step six using deionized water to obtain a carbon-based hierarchical subporous bioelectrode material. The desalting and impurity removal process is as follows: First, the electrode material is washed with deionized water until neutral, and then dried to complete the desalting; the desalted electrode material is soaked in an organic solvent for 4 hours to complete the impurity removal, and finally ultrasonically cleaned in deionized water for 40 minutes and dried; the organic solvent is anhydrous ethanol.

[0038] Example 2: The preparation method of the carbon-based hierarchical subporous bioelectrode material of biomass-resin composite material in this embodiment is carried out according to the following steps: I. Preparation of Resin Precursors: ① Phenolic resin is synthesized using formaldehyde and phenol, and melamine is added to the phenolic resin for formaldehyde substitution modification to obtain melamine-modified phenolic resin. The process for synthesizing phenolic resin is as follows: formaldehyde and phenol are placed in a three-necked flask, an alkaline catalyst is added, and the mixture is refluxed under a water bath heating condition at 80°C for 0.5 hours; the molar ratio of formaldehyde to phenol is 1.5:1. The process for formaldehyde substitution modification is as follows: melamine is added to the phenolic resin, and the mixture is refluxed under a water bath heating condition at 80°C for 2 hours. The alkaline catalyst is a 20% NaOH solution; the alkaline catalyst is 15% of the mass of phenol, and the melamine is 25% of the mass of phenol. ② Preparation of iron-nitrogen co-doped resin: Cool the melamine-modified phenolic resin from step ① to 50°C, add the pre-dissolved iron source solution, and react for 10-60 minutes to obtain the iron-nitrogen co-doped resin. The iron source in the iron source solution is acetylacetone iron; The solvent in the iron source solution is N,N-dimethylformamide; The mass of the iron source in the iron source solution is 3% of the mass of phenol; II. Biomass Precursor Preparation After washing and drying, the biomass is pulverized to obtain 150μm biomass powder; The biomass is spinach: The drying process is freeze-drying at -50°C for 24 hours. III. Activation of Biomass Precursors The biomass powder obtained in step two was co-dispersed with the activator in deionized water to obtain a mixture. The mixture was stirred at 60°C for 10 hours and then freeze-dried to obtain the activated biomass precursor. The freeze-drying temperature is -50°C and the drying time is 48 hours.

[0039] The activator is KOH; The mass ratio of the biomass powder to the activator is 1:3; IV. Biomass precursor precarbonization The activated biomass precursor obtained in step three is pre-carbonized to obtain a pre-carbonized biomass precursor. The pre-carbonization process is as follows: in an inert gas atmosphere, at 5°C for 5 minutes... -1 The temperature was heated to 400°C and maintained for 60 minutes at a rate of [missing information]; the inert gas was N2, and the inert gas flow rate was 100 mL / min. -1 ; V. Preparation of Composite Carbonization Precursors 12g of the iron-nitrogen co-doped resin obtained in step one, 5g of the pre-carbonized biomass precursor obtained in step four, and 1.2g of plastic microparticle sacrificial template were mixed evenly, and the mixture was cured at 140°C for 6 hours to obtain the composite carbonized precursor. The sacrificial template for the plastic microparticles is made of plastic microparticles, specifically polyamide 6. VI. Carrier Gas Protected Carbonization High-Temperature Pyrolysis Under an inert gas atmosphere, the composite carbonization precursor obtained in step five was heated at 5°C for 1 minute. -1 The temperature was increased to 900℃ at a heating rate, and the material was pyrolyzed at high temperature for 2 hours to obtain the high-temperature pyrolysis material. VII. Desalting and Impurity Removal of Carbonized Electrode Desalting and impurity removal were performed on the high-temperature pyrolysis material obtained in step six using deionized water to obtain a carbon-based hierarchical subporous bioelectrode material. The desalting and impurity removal process is as follows: First, the electrode material is washed with deionized water until neutral, and then dried to complete the desalting; the desalted electrode material is soaked in an organic solvent for 4 hours to complete the impurity removal, and finally ultrasonically cleaned in deionized water for 40 minutes and dried; the organic solvent is anhydrous ethanol.

[0040] Example 3: The preparation method of the carbon-based hierarchical subporous bioelectrode material of biomass-resin composite material in this embodiment is carried out according to the following steps: I. Preparation of Resin Precursors: ① Phenolic resin is synthesized using formaldehyde and phenol, and melamine is added to the phenolic resin for formaldehyde substitution modification to obtain melamine-modified phenolic resin. The process for synthesizing phenolic resin is as follows: formaldehyde and phenol are placed in a three-necked flask, an alkaline catalyst is added, and the mixture is refluxed under a water bath heating condition at 80°C for 0.5 hours; the molar ratio of formaldehyde to phenol is 1.5:1. The process for formaldehyde substitution modification is as follows: melamine is added to the phenolic resin, and the mixture is refluxed under a water bath heating condition at 80°C for 2 hours. The alkaline catalyst is a 20% NaOH solution; the alkaline catalyst is 15% of the mass of phenol, and the melamine is 25% of the mass of phenol. ② Preparation of iron-nitrogen co-doped resin: Cool the melamine-modified phenolic resin from step ① to 50°C, add the pre-dissolved iron source solution, and react for 10-60 minutes to obtain the iron-nitrogen co-doped resin. The iron source in the iron source solution is acetylacetone iron; The solvent in the iron source solution is N,N-dimethylformamide; The mass of the iron source in the iron source solution is 3% of the mass of phenol; II. Biomass Precursor Preparation After washing and drying, the biomass is pulverized to obtain 150μm biomass powder; The biomass is *Ulva prolifera*. The drying process is freeze-drying at -50°C for 24 hours. III. Activation of Biomass Precursors The biomass powder obtained in step two was co-dispersed with the activator in deionized water to obtain a mixture. The mixture was stirred at 60°C for 10 hours and then freeze-dried to obtain the activated biomass precursor. The freeze-drying temperature is -50°C and the drying time is 48 hours.

[0041] The activator is KOH; The mass ratio of the biomass powder to the activator is 1:3; IV. Biomass precursor precarbonization The activated biomass precursor obtained in step three is pre-carbonized to obtain a pre-carbonized biomass precursor. The pre-carbonization process is as follows: in an inert gas atmosphere, at 5°C for 5 minutes... -1 The temperature was heated to 400°C and maintained for 60 minutes at a rate of [missing information]; the inert gas was N2, and the inert gas flow rate was 100 mL / min. -1 ; V. Preparation of Composite Carbonization Precursors 12g of the iron-nitrogen co-doped resin obtained in step one, 6g of the pre-carbonized biomass precursor obtained in step four, and 1.2g of plastic microparticle sacrificial template were mixed evenly, and the mixture was cured at 140°C for 6 hours to obtain the composite carbonized precursor. The sacrificial template for the plastic microparticles is made of plastic microparticles, specifically polyamide 6. VI. Carrier Gas Protected Carbonization High-Temperature Pyrolysis Under an inert gas atmosphere, the composite carbonization precursor obtained in step five was heated at 5°C for 1 minute. -1 The temperature was increased to 900℃ at a heating rate, and the material was pyrolyzed at high temperature for 2 hours to obtain the high-temperature pyrolysis material. VII. Desalting and Impurity Removal of Carbonized Electrode Desalting and impurity removal were performed on the high-temperature pyrolysis material obtained in step six using deionized water to obtain a carbon-based hierarchical subporous bioelectrode material. The desalting and impurity removal process is as follows: First, the electrode material is washed with deionized water until neutral, and then dried to complete the desalting; the desalted electrode material is soaked in an organic solvent for 4 hours to complete the impurity removal, and finally ultrasonically cleaned in deionized water for 40 minutes and dried; the organic solvent is anhydrous ethanol.

[0042] The microbial electrochemical systems in Examples 1-3 specifically include: (1) A dual-chamber microbial electrochemical system, the volume of the cathode chamber and the anode chamber can be adjusted as needed. The cathode chamber and the anode chamber are separated by a cation exchange membrane. The anode material is the carbon-based hierarchical subporous bioelectrode material of Examples 1-3, and the cathode material is a carbon brush. The system is a dual-chamber reactor, with the anode chamber being 4×4×2cm and the cathode chamber being 4×4×4cm. (2) The anode inlet water is 1g / L -l Sodium acetate, 50 mmol / L -1 phosphate buffer solution, 2 ml / L -1 Vitamins and 1.25 ml / L -1 Trace elements were inoculated using domestic sewage (20% of the volume of the anolyte solution); the catholyte solution was 50 mmol / L. -1 50 mmol / L phosphate buffer solution -1 Potassium ferricyanide solution; (3) Water is introduced into the cathode and anode respectively. The system is operated in batch mode at 28~31℃. When the output voltage drops to 10~15%, the anolyte and catholyte are replaced. The system can be further enriched with microorganisms at the anode by continuing to run the system. (4) During system operation, electrons generated by anode microorganisms are transferred to the cathode for utilization. The microorganisms include... Geobacter sp .,Desulfovibrio sp Bacteria sp . The reactors were started with an external resistance of 1000Ω and operated at a temperature of 30±1°C. The acclimation of the anolyte biofilm was achieved by gradually decreasing the resistance (1000Ω, 510Ω, 415Ω, 300Ω, 210Ω). The output voltage of each reactor was recorded every 30 minutes using a data acquisition system. When the output voltage dropped below 100mV, the anolyte and catholyte were replaced.

[0043] Figure 1 The diagram shows the microbial electrochemical system (MES system) in Examples 1-3: where 1-external resistance, 2-anode chamber, 3-anode material, 4-cathode chamber, 5-cathode material, and 6-ion exchange membrane; The anodes of the microbial electrochemical systems in control groups 1-3 differed from those in Examples 1-3, while the other components of the microbial electrochemical systems were the same as in Examples 1-3. The anode in control group 1 was a carbon felt; the anode in control group 3 was a carbon brush; the anode in control group 2 was prepared by: curing the iron-nitrogen co-doped resin obtained in step one of Example 1 at 140°C for 6 hours, followed by carbonization; the carbonization process was carried out at 5°C for 5 minutes. -1 Heat to 900℃ at a rising rate and hold for 3 hours; Figure 2 Scanning electron microscope image of the carbon-based hierarchical subporous bioelectrode material prepared for control group 2. Figure 2 A magnified view of a portion containing surface holes; Figure 3 A scanning electron microscope image of the carbon-based hierarchical subporous bioelectrode material prepared in Example 1; Figure 4 This is a scanning electron microscope image of the carbon-based hierarchical subporous bioelectrode material prepared in Example 2; Figure 5 This is a scanning electron microscope image of the carbon-based hierarchical subporous bioelectrode material prepared in Example 3; Figures 2-5 As can be seen, the carbon-based hierarchical subporous bioelectrode material prepared in the examples has hierarchical channels ranging from nanometers to hundreds of micrometers. The carbonized resin electrode has a macroporous structure (597.7 ± 111.8 μm), with concave surfaces of carbon skeleton distribution diameter of 63.8 ± 16.5 μm between adjacent pores. The biomass-resin composite electrode has a hierarchical subporous structure, including macropores on the surface (surface pores in the figure, 80–150 μm), mesopores on the pore walls of the surface pores (pore wall pores in the figure, 20–30 μm), and micropores on the carbon skeleton (0.5–3 μm). These porous structures can respectively provide conditions for mass transport (hundreds of micrometers to millimeters of macroscopic channels), electroactive microbial attachment (1 to 100 micrometers), and catalytic conversion of "chemical energy to electrical energy" (nanometers to 1 micrometer).

[0044] Figure 6 The cyclic voltammetry curves of the carbon-based hierarchical subporous bioelectrode materials prepared in the examples are shown. The electrode materials in Examples 1-3 have excellent capacitance characteristics, with capacitance values ​​10-45 times higher than carbon cloth (control group 1) and 4-17 times higher than the electrode without biomass (control group 2).

[0045] Figure 7 The diagram shows the cumulative charge and coulombic efficiency of the microbial electrochemical system during a single cycle in the examples. Figure 8 The power density curve of the biofilm formed on the carbon-based hierarchical subporous bioelectrode material in the embodiment is shown. Figure 9 The diagram shows the capacitance charge on the carbon-based hierarchical subporous bioelectrode material in the embodiment. Figure 10 This is a diagram of biomass on the carbon-based hierarchical subporous bioelectrode material in the embodiment; Figure 11 The diagram shows the community composition and abundance on the carbon-based hierarchical subporous bioelectrode material in the examples.

[0046] During the operation of the MES system in Example 1, the average accumulated charge per cycle was 154 ± 9.8 C, and the average coulombic efficiency was 59 ± 8.6%. After the system stabilized, the polarization curve and power density were measured using a variable resistance box. The maximum power density of the system reached 4100 ± 113 mW / m². -2 The maximum current density reached 12.5 ± 0.1 Am. -2The capacitance charge in the bioanode is 1256 ± 86 C m. –2 The biomass domesticated on the anode was 1298.6 μg / cm³. -2 The total abundance of electrogenic bacteria in the electroactive biofilm was 75%.

[0047] During the operation of the MES system in Example 2, the average cumulative charge per cycle was 156 ± 5.1 C, and the average coulombic efficiency was 60 ± 9.3%. The maximum power density of the system reached 5253 ± 7 mW / m². -2 The maximum current density reached 19 ± 0.9 Am. -2 The capacitance charge in the bioanode is 2319 ± 97 C m. –2 The biomass domesticated on the anode was 1310.8 μg / cm³. -2 The total abundance of electrogenic bacteria in the electroactive biofilm was 74%.

[0048] During the operation of the MES system in Example 3, the average cumulative charge per cycle was 158 ± 5.3 C, and the average coulombic efficiency was 61 ± 8.1%. The maximum power density of the system reached 6138 ± 118 mW / m³. -2 The maximum current density reached 21.8 ± 0.1 Am. -2 The capacitance charge in the bioanode is 3577 ± 160.3 C m. -2 The biomass domesticated on the anode was 1873.7 μg / cm³. -2 The total abundance of electrogenic bacteria in the electroactive biofilm was 85%.

[0049] In control group 1, the average cumulative charge per cycle of the MES system was 138 ± 9.9 C, and the average coulombic efficiency was 55 ± 5.1%. The maximum power density of the system was 1870 ± 91 mW / m³. -2 The maximum current density is 5.1 ± 0.84 Am. -2 The capacitance charge in the bioanode is 13.3 ± 3 C m. –2 The biomass domesticated on the anode was 324.3 μg / cm³. -2 The total abundance of electrogenic bacteria in the electroactive biofilm was 69%.

[0050] In control group 2, the MES system had an average cumulative charge of 144 ± 7.7 C per cycle during operation, and an average coulombic efficiency of 57 ± 6.4%. The maximum power density reached 2652 ± 148 mW / m². -2 The maximum current density reached 6 ± 0.1 Am. -2 The capacitance charge in the bioanode is 414 ± 18 C m. –2The biomass domesticated on the anode was 324.3 μg cm³. -2 The total abundance of electrogenic bacteria in the electroactive biofilm was 71%.

[0051] The maximum power density of control group 3 was 3980 ± 53 mW / m³. -2 The maximum current density is 8 ± 0.4 A m. -2 .

Claims

1. A method for preparing a carbon-based hierarchical subporous bioelectrode material of biomass-resin composite material, characterized in that: The preparation method of the carbon-based hierarchical subporous bioelectrode material of biomass-resin composite material is carried out according to the following steps: I. Preparation of Resin Precursors: ① Phenolic resin is synthesized using formaldehyde and phenol, and melamine is added to the phenolic resin for formaldehyde substitution modification to obtain melamine-modified phenolic resin. The process for synthesizing phenolic resin is as follows: formaldehyde and phenol are placed in a three-necked flask, an alkaline catalyst is added, and the mixture is refluxed under a water bath heating condition of 75~85℃ for 0.5~1 hours. The molar ratio of formaldehyde to phenol is 1.3~1.8:1; The alkaline catalyst is a 20% (w / w) NaOH solution; The alkaline catalyst is 5% to 15% of the mass of phenol; The melamine is 5% to 30% of the mass of phenol; The process for formaldehyde substitution modification is as follows: melamine is added to phenolic resin, and the mixture is refluxed under water bath heating conditions of 75~85℃ for 1.5~2 hours. ② Preparation of iron-nitrogen co-doped resin: Cool the melamine-modified phenolic resin from step ① to 25~50℃, add the pre-dissolved iron source solution, and react for 10~60 minutes to obtain iron-nitrogen co-doped resin. The mass of the iron source in the iron source solution is 1% to 12% of the mass of phenol; II. Biomass Precursor Preparation After washing and drying, the biomass is pulverized to obtain biomass powder with a mesh size of 60-100. III. Activation of Biomass Precursors The biomass powder obtained in step two is co-dispersed with the activator in deionized water to obtain a mixture. The mixture is stirred at 30-60°C for 8-12 hours and then freeze-dried to obtain the activated biomass precursor. The mass ratio of the biomass powder to the activator is 1:0.5~4; IV. Biomass precursor precarbonization The activated biomass precursor obtained in step three is pre-carbonized to obtain a pre-carbonized biomass precursor. The pre-carbonization process is as follows: in an inert gas atmosphere, at 1~5℃·min -1 Heat at a rate of 300~400℃ and maintain for 30~60 minutes; The inert gas is N2; The inert gas flow rate is 80~120 mL·min. -1 ; V. Preparation of Composite Carbonization Precursors The iron-nitrogen co-doped resin obtained in step one, the pre-carbonized biomass precursor obtained in step four, and the plastic microparticle sacrificial template are mixed evenly, and the mixture is cured at 90~140℃ for 6~14 hours to obtain the composite carbonized precursor. The sacrificial template of the plastic microparticles is 1-10% of the mass of the iron-nitrogen co-doped resin; The pre-carbonized biomass precursor is 30-70% of the mass of the iron-nitrogen co-doped resin; The sacrificial template for the plastic microparticles is a plastic microparticle; The plastic microparticles are made of polyethylene, polylactic acid, polyamide, polystyrene, polyoxymethylene, or polymethyl methacrylate. VI. Carrier Gas Protected Carbonization High-Temperature Pyrolysis Under an inert gas atmosphere, the composite carbonization precursor obtained in step five was subjected to an inert gas atmosphere at 1~8℃·min. -1 The temperature is increased to 700~1000℃ at a heating rate, and then pyrolyzed at high temperature for 1~3 hours to obtain high-temperature pyrolysis material; VII. Desalting and Impurity Removal of Carbonized Electrode The high-temperature pyrolysis material obtained in step six was desalted and impurities removed using deionized water to obtain a carbon-based hierarchical subporous bioelectrode material.

2. The method for preparing the carbon-based hierarchical subporous bioelectrode material of biomass-resin composite material according to claim 1, characterized in that: In step 1②, the iron source solution contains FeCl3, FeCl2, Fe(OAc)2, iron acetylacetone, or iron phthalate.

3. The method for preparing the carbon-based hierarchical subporous bioelectrode material of biomass-resin composite material according to claim 1, characterized in that: The solvent in the iron source solution described in step 1② is deionized water, N,N-dimethylformamide, or dimethyl sulfoxide.

4. The method for preparing the carbon-based hierarchical subporous bioelectrode material of biomass-resin composite material according to claim 1, characterized in that: The biomass mentioned in step two is spinach, wood ear fungus, shiitake mushroom, laver, seaweed, sea lettuce, or pumpkin seeds.

5. The method for preparing the carbon-based hierarchical subporous bioelectrode material of biomass-resin composite material according to claim 1, characterized in that: The drying process described in step two is freeze drying at -20 to -80°C for 24 to 48 hours; or drying at 40 to 60°C for 24 to 48 hours.

6. The method for preparing the carbon-based hierarchical subporous bioelectrode material of biomass-resin composite material according to claim 1, characterized in that: The freeze-drying temperature in step three is -20 to -80°C, and the drying time is 24 to 48 hours.

7. The method for preparing the carbon-based hierarchical subporous bioelectrode material of biomass-resin composite material according to claim 1, characterized in that: The activator mentioned in step three is ZnCl2, KOH, KHCO3, K2FeO4, or NaOH.

8. The method for preparing the carbon-based hierarchical subporous bioelectrode material of biomass-resin composite material according to claim 1, characterized in that: The desalting and impurity removal process described in step seven is as follows: First, the electrode material is washed with deionized water until neutral, and then dried to complete the desalting; the desalted electrode material is soaked in an organic solvent for 1 to 6 hours to complete the impurity removal, and finally ultrasonically cleaned with deionized water for 20 to 60 minutes and dried. The organic solvent is anhydrous ethanol or acetone.

Citation Information

Patent Citations

  • Double-layer porous Fe-N co-doped carbon material and preparation method and application thereof

    CN108695521A

  • Sodium-ion battery anode material and preparation method thereof

    CN116666581A

  • Silicon-carbon material and preparation method thereof, porous carbon substrate, negative electrode material and battery

    CN119812286A